Peningkatan Minat Baca Masyarakat Melalui Wisata Leterasi - Hidayati, Istania Widayati; Usman, Nurodin (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2020)
The purpose of this community service is to increase children's interest in reading. Nowadays, children have been busy with their gadgets and tend to have low literacy. The basic problem is the dominance of gadgets in the daily lives of children in Pondok Rejo Asri Housing in addition to the low literacy culture. The solutions offered are socialization, training, practice, mentoring and the establishment of a reading park so that children have higher linguistic intelligence and have a passion for better reading and writing. Reading, which has been assumed to be boring, will change its paradigm with something unique and interesting.Â  Literacy activities to foster children's reading interest in this service are carried out in several stages, namely: outbound, socialization, talk shows with young writers, magic clowns and outbound literacy. The last is to establish a children's reading park: "Peluk Bukuâ€.